Implementation of Local Content-Based E-Modules to Strengthen Religious Moderation in Elementary Madrasah Teacher Education Study Programs - Miftahul Husni; Siti Fatimah; Rachmi Destiani; Ahmadani Ferdiyan; Faisal Faisal (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
College students are vulnerable to radicalism and the spread of hoaxes that may trigger conflict and disrupt learning. Therefore, this study aimed to examine the effect of implementing local content-based e-modules on strengthening religious moderation among students of the PGMI Study Program. This study employed a quantitative approach with an experimental design, while the sample was selected through purposive sampling. Data were collected using a questionnaire measuring religious moderation based on indicators of acceptance of local culture aligned with Pancasila values. The data were analyzed using inferential statistical tests to determine the significance of the effect. The findings revealed a significant influence of local content-based e-modules on strengthening students’ religious moderation, with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The e-modules were proven effective not only as teaching materials but also in improving students’ understanding and attitudes toward religious moderation, including tolerance and interreligious harmony. The study concludes that local content-based e-modules play an important role in strengthening religious moderation among college students. The implications highlight the importance of integrating religious moderation values into the curriculum through curriculum revitalization, collaboration with religious moderation centers, and lecturer training programs.